노인의 성별에 따른 행복감에 영향을 주는 요인 - 홍주연(Ju-Youn Hong); 김환희(Hwan-Hui Kim) (한국콘텐츠학회 논문지, 20(4), 2020)
This study aimed to assess the factors affecting the level of happiness and a sense of happiness among senior men and women, including sociodemographic characteristics, health behavior, subjective health level, and healthcare utilization, using the 2017 Community Health Survey (CHS). A total of 67,835 older adults were enrolled for the study, 27,979 males and 39,856 females. The results showed that education level and total household income affected the happiness in female elderly, while having a spouse increased happiness in male elderly. In addition, both male elderly and female felt a great of happiness when they had good health behaviors, perceived themselves to be in good health, and had no restrictions with healthcare utilization. Subjective health status and healthcare utilization seem to have a substantial impact on happiness because older adulthood is a period marked with increased physical vulnerability compared to other age groups due to diminished physiological functions. Based on these results, the government should expand subsidies for welfare for the aged to provide lifelong education opportunities and the existing elderly education and programs in health-related organizations should reflect the characteristics of the elderly. Furthermore, social service systems and programs related to the elderly should be re-evaluated so as to develop services and programs tailored to the elderly to promote their happiness more effectively. 본 연구는 2017년도 지역사회건강조사 자료를 이용하여 65세 이상 남성노인과 여성노인의 인구사회학적 특성, 건강행태 및 주관적 건강수준, 의료이용 등에 따른 행복감 수준과 행복감에 영향을 미치는 요인을 평가해 보고자 하였다. 연구대상은 남성노인 27,979명, 여성노인 39,856명으로 총 67,835명으로 선정하였다. 연구결과 여성노인은 남성노인보다 교육수준과 가구 총 소득이 행복감에 영향을 주었고 남성노인은 배우자 유무가 행복감에 영향을 주어 배우자가 있는 경우 행복감 수준이 높았다. 그리고 남성노인과 여성노인 모두 건강행태 및 주관적 건강수준이 좋을 때 의료이용에 제한이 없을 때 행복감을 크게 느꼈다. 이는 노년기에는 신체 생리적인 기능의 감퇴로 인하여 다른 연령집단에 비해 신체적 건강에 대한 취약성이 증가하는 시기이므로 건강행태 및 주관적 건강수준, 의료이용이 큰 영향을 미치는 것으로 생각된다. 이러한 결과를 토대로 국가적 차원에서 노인복지를 위한 제정을 확대하여 노인의 성별 특성에 맞는 평생교육의 기회를 제공해야 하며 현재 운영되고 있는 노인교육, 건강관련기관의 프로그램을 노인의 특성에 맞게 운영되어야 할 것이다. 또한 노인과 관련된 사회서비스 체계 및 프로그램의 재평가 해 노년의 행복감을 좀 더 효과적으로 증진시킬 수 있는 서비스와 프로그램 개발을 위한 노력이 필요하다.